2005
DOI: 10.1074/jbc.m501452200
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Down-regulates Cellular Glutathione Peroxidase (GPx1) by Decreasing Translation

Abstract: Hyperhomocysteinemia contributes to vascular dysfunction and an increase in the risk of cardiovascular disease. An elevated level of homocysteine in vivo and in cell culture systems results in a decrease in the activity of cellular glutathione peroxidase (GPx1), an intracellular antioxidant enzyme that reduces hydrogen peroxide and lipid peroxides. In this study, we show that homocysteine interferes with GPx1 protein expression without affecting transcript levels. Expression of the selenocysteine (SEC)-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 48 publications
2
96
0
2
Order By: Relevance
“…Handy et al [34] previously demonstrated that homocysteine decreases glutathione peroxidase activity by altering the specific translational mechanism essential for the synthesis of this selenocysteine-containing protein. Superoxide dismutase protein levels in the heart were reduced in a dog model [35] and in a rat model of chronic hyperhomocysteinemia [36].…”
Section: Discussionmentioning
confidence: 99%
“…Handy et al [34] previously demonstrated that homocysteine decreases glutathione peroxidase activity by altering the specific translational mechanism essential for the synthesis of this selenocysteine-containing protein. Superoxide dismutase protein levels in the heart were reduced in a dog model [35] and in a rat model of chronic hyperhomocysteinemia [36].…”
Section: Discussionmentioning
confidence: 99%
“…COS-7 cells, which do not express endogenous GC, were plated in 6-well tissue culture dishes and transfected with 5 g of DNA for 4 h with Lipofectamine 2000 TM (Invitrogen) (24). After this time, medium was replaced with full growth media, and experiments were performed after 48 h.…”
Section: Methodsmentioning
confidence: 99%
“…ROS are important intracellular second messengers that mediate the production of inflammatory cytokines (Gorowara et al 1998). Abundant evidence indicated that excessive Hcy in endothelial cells induces endothelial dysfunction through the inhibition of arginine transport (Jin et al 2007), elevates ROS levels through autooxidation, and diminishes the activities of antioxidative enzymes, such as glutathione peroxidase-1 (Handy et al 2005) and superoxide dismutase (Yamamoto et al 2000). Furthermore, recent studies indicate that Hcy induces the production of superoxide anion (AlvarezMaqueda et al 2004;Au-Yeung et al 2006), exerts important effects on cellular NO production (Tsen et al 2003;Zhang et al 2000), and interferes with de novo GSH synthesis Figure 11 Schematic representation of the involvement of miR-137 and miR-2008 in the host-pathogen interaction by cotargeting AjBHMT.…”
Section: Discussionmentioning
confidence: 99%